Innovation efforts and performances of Brazilian firms - Lopes Santos, David Ferreira [UNESP]; Cruz Basso, Leonardo Fernando; Kimura, Herbert; Kayo, Eduardo Kazuo (Elsevier B.V., 2014)
We analyze the relationship between innovation and firms' performance in Brazil using a comprehensive database that cross-references innovation information by PINTEC (Technological Innovation Research) of the IBGE (Brazilian Institute of Geography and Statistics) and financial information from Serasa and Gazeta Mercantil. Results from the structural equation modeling suggest that variables associating with investments in innovation, which are connected to the innovative effort of a company, do not explain financial performance significantly. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Innovation; Performance; Research and Development; Brazilian firms